Insight Into Inflammasome Signaling: Implications for Toxoplasma gondii Infection - Wang, Yang; Zhu, Jinjin; Cao, Yuanyuan; Shen, Jilong; Yu, Li (Frontiers in Immunology, 2020)
Inflammasomes are multimeric protein complexes regulating the innate immune response to invading pathogens or stress stimuli. Recent studies have reported that nucleotide-binding leucine-rich repeat-containing (NLRs) proteins and DNA sensor absent in melanoma 2 (AIM2) serve as inflammasome sentinels, whose stimulation leads to the proteolytic activation of caspase-1, proinflammatory cytokine secretion, and pyroptotic cell death. Toxoplasma gondii, an obligate intracellular parasite of phylum Apicomplexans, is reportedly involved in NLRP1, NLRP3 and AIM2 inflammasomes activation; however, mechanistic evidence regarding the activation of these complexes is preliminary. This review describes the current understanding of inflammasome signaling in rodent and human models of T. gondii infection.